Penggunaan Aplikasi Tata Surat Dalam Pengelolaan Surat di MTsN 1 Kota Palangka Raya - Sandi, Kurnia; Aliyah, Muhumatul; Waningsih, Sri; Bhekti, Siti Maria Noorlaila Yunia; Sapuadi, Sapuadi (Institut Agama Islam Negeri Palangka Raya, 2023)
Penelitian ini berjudul